Hypoxia-induced cancer cell reprogramming: a review on how cancer stem cells arise - Abd, Genevieve M.; Laird, Madison C.; Ku, Jennifer C.; Li, Yong (Frontiers in Oncology, 2023)
Cancer stem cells are a subset of cells within the tumor that possess the ability to self-renew as well as differentiate into different cancer cell lineages. The exact mechanisms by which cancer stem cells arise is still not completely understood. However, current research suggests that cancer stem cells may originate from normal stem cells that have undergone genetic mutations or epigenetic changes. A more recent discovery is the dedifferentiation of cancer cells to stem-like cells. These stem-like cells have been found to express and even upregulate induced pluripotent stem cell markers known as Yamanaka factors. Here we discuss developments in how cancer stem cells arise and consider how environmental factors, such as hypoxia plays a key role in promoting the progression of cancer stem cells and their metastasis through Yamanaka reprogramming factors. Understanding the mechanisms that give rise to these cells could have important implications for the development of new strategies in cancer treatments and therapies.